Early suppression of antiviral host response and protocadherins by SARS-CoV-2 Spike protein in THP-1-derived macrophage-like cells - Miltner, Noémi; Linkner, Tamás Richárd; Ambrus, Viktor; Al-Muffti, Aya S.; Ahmad, Hala; Mótyán, János András; Benkő, Szilvia; Tőzsér, József; Mahdi, Mohamed (Frontiers in Immunology, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of coronavirus disease-19 (COVID-19). The spike protein (S) of SARS-CoV-2 plays a crucial role in mediating viral infectivity; hence, in an extensive effort to curb the pandemic, many urgently approved vaccines rely on the expression of the S protein, aiming to induce a humoral and cellular response to protect against the infection. Given the very limited information about the effects of intracellular expression of the S protein in host cells, we aimed to characterize the early cellular transcriptomic changes induced by expression of the S protein in THP-1-derived macrophage-like cells. Results showed that a wide variety of genes were differentially expressed, products of which are mainly involved in cell adhesion, homeostasis, and most notably, antiviral and immune responses, depicted by significant downregulation of protocadherins and type I alpha interferons. Our study highlights the intrinsic pathogenic role of the S protein and sheds some light on the potential drawbacks of its utilization in the context of vaccination strategies.